Zabbix network monitoring essentials - Haas, Christoph; Safari eBooks ([Birmingham, U.K.?] : Packt Pub., 2013)
"If you're a professional system and network administrator who is responsible for the reliable operation of an IT network then this video course is for you. All you need to know is how to manage Linux systems and network services. Additional use of scripting languages such as Python, Perl, or Ruby can extend Zabbix's functionality for monitoring your own custom services. Packt video courses are designed to cover the breadth of the topic in short, hands-on, task-based videos. Each course is divided into short manageable sections, so you can watch the whole thing or jump to the bit you need. The focus is on practical instructions and screencasts showing you how to get the job done. A practical video course with step-by-step instructions and an example-driven approach for setting up and monitoring your network using Zabbix."--Resource description page.
Presenter, Christoph Haas.
Title from title screen.
Date of publication from resource description page (Safari, viewed Nov. 8, 2013).
Keywords: Computer networks -- Security measures; Computer security; Computer networks; Electronic books